Specifics of Geotechnical Risk Control in Underground Structure Design - J. X, Mamirov (International Journal of Formal Education, 2024)
Developing underground spaces presents complex and hazardous situations that can lead to accidents, primarily due to potential geotechnical risks. Effective risk control involves thorough execution and analysis at all design stages, starting early in the process. Understanding the characteristics of the surrounding rock mass helps identify the likelihood of adverse events during construction and operation. The aim of qualitative risk analysis is to pinpoint risk factors in underground construction. The total geotechnical risk should be quantified at the design stage by summing potential risks. Establishing a methodology for managing these risks is crucial for early-stage assessment and for proposing mitigation measures. This article outlines such a methodology and demonstrates its effectiveness in accident prevention during underground construction.